Strategic sustainability integration: Merging management tools to support business model decisions - Silvestre, W.; Fonseca, A.; Morioka, S. N. (Business Strategy and the Environment, 2022)
Despite the competitive advantages of sustainable business models, developing management solutions to systematically support sustainability integration into organizational strategy is still a challenging approach for most organizations. Based on a critical analysis of existing tools to support sustainable business models, the present paper describes the development of a practical management tool to guide the strategic integration of sustainability in organizational business models. The proposed management tool results from the synergistic combination of the Sustainable Value Exchange Matrix and the Integrative Sustainable Intelligence Model, in a cyclic and continuous process supported by the periodic diagnosis of the key organizational factors with relevance for successful sustainability integration processes. The management tool described in this paper is expected to guide the strategic adaptation of organizations toward results with a positive impact on sustainability, with an effective contribution to the development of more sustainable business models.